The association between suicidal ideation and lifetime suicide attempts is strongest at low levels of depression. (December 2018) - Rogers, Megan L.; Ringer, Fallon B.; Joiner, Thomas E.
Highlights: Suicidal ideation and depression alone are poor predictors of suicide attempts (SA). The lethargy associated with depression may serve as a protective factor against SA. A sample of 739 psychiatric outpatients completed self-report measures. The interaction between suicidal ideation and depression predicted lifetime SA. The association between suicidal ideation and SA was strongest at low depression levels. Abstract: Suicidal ideation and depression alone are poor predictors of subsequent engagement in suicidal behavior. Evidence suggests, however, that the lethargy associated with depression may serve as a protective factor against suicide attempts. The purpose of this study was to examine whether suicidal ideation and depression symptoms interact in relation to lifetime suicide attempts among a sample of psychiatric outpatients. A sample of 739 psychiatric outpatients ( Mage  = 27.26, 60.8% female, 73.3% White/European American) from a university-affiliated clinic completed a battery of self-report measures prior to their initial intake appointments. Consistent with hypotheses, a significant interaction emerged between suicidal ideation and depression symptoms in association with lifetime suicide attempts, such that the relationship between suicidal ideation and lifetime suicide attempts was strongest at low, as opposed to high, levels of depression. These findings align with previous research suggesting that lethargy may be a protective factor against suicide attempts, and conversely, that heightened arousal may serve as a suicide risk factor. Our results also point to a configuration of suicidal ideation and depression symptoms that might reflect higher suicide risk.